Temporary oral anticoagulation after MitraClip: a strategy to lower the incidence of post-procedural stroke? - Geis, Nicolas; Raake, Philip; Kiriakou, Christina; Mereles, Derliz; Frankenstein, Lutz; Abu Sharar, Haitham; Chorianopoulos, Emmanuel; Katus, Hugo; Bekeredjian, Raffi; Pleger, Sven Torsten (Acta cardiologica, 2020)
Incidence of stroke within 30 days after percutaneous mitral valve repair using the MitraClip varies from 0.7% and 2.6% between registries. Standard medical treatment after the MitraClip procedure, in the absence of risk factors requiring antithrombotic therapy such as atrial fibrillation, is dual antiplatelet therapy using aspirin and clopidogrel. ESC/EACTS and ACC/AHA surgical guidelines show a Class IIa indication for temporary antithrombotic therapy after mitral valve repair/bioprosthetic valve replacement within the first three months even in patients with no additional risk factors.
Published online: 16 Jan 2019
Gesehen am 27.02.2020